Evolving Standards in Prosthetic Heart Valve Assessment With Cardiovascular Imaging: Key Changes in the 2024 American Society of Echocardiography Guidelines - Fraser Graham, MD; Stephen Dobbin, MD; Maala Sooriyakanthan, RDMS; Wendy Tsang, MD, SM (Structural Heart)
The American Society of Echocardiography recommendations published in 2024 for evaluating prosthetic heart valve (PHV) function with cardiovascular imaging include new recommendations for the use of cardiac magnetic resonance imaging, cardiac computed tomography, and cardiac positron emission tomography. Additionally, they now provide normative echocardiographic values for right-sided PHVs and transcatheter heart valves in native valves and when used for valve-in-valve procedures. Furthermore, the recommendations include definitions to improve the recognition and classification of prosthetic heart valve dysfunction. The aim of this review is to summarize these key changes compared to the 2009 update and to include useful tables and figures to aid the reader in assessment of PHV function.